2011
DOI: 10.3390/ijms12010506
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical and Cellular Basis for Nutraceutical Strategies to Attenuate Neurodegeneration in Parkinson’s Disease

Abstract: Future therapeutic intervention that could effectively decelerate the rate of degeneration within the substantia nigra pars compacta (SNc) could add years of mobility and reduce morbidity associated with Parkinson’s disease (PD). Neurodegenerative decline associated with PD is distinguished by extensive damage to SNc dopaminergic (DAergic) neurons and decay of the striatal tract. While genetic mutations or environmental toxins can precipitate pathology, progressive degenerative succession involves a gradual de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 536 publications
(338 reference statements)
0
20
0
Order By: Relevance
“…Nutraceuticals are food or components of food that provide medicinal or health benefits (Tapas et al, 2008). Dietary intake of flavonoids is used for the treatment of Parkinson disease (Mazzio et al, 2011). Clinical trials have linked increasing intake of flavonoids with a reduced occurrence of breast cancer in humans (Bosetti et al, 2005).…”
Section: Volume 40mentioning
confidence: 99%
“…Nutraceuticals are food or components of food that provide medicinal or health benefits (Tapas et al, 2008). Dietary intake of flavonoids is used for the treatment of Parkinson disease (Mazzio et al, 2011). Clinical trials have linked increasing intake of flavonoids with a reduced occurrence of breast cancer in humans (Bosetti et al, 2005).…”
Section: Volume 40mentioning
confidence: 99%
“…Considering the cascade of degenerative events of diseases such as AD and PD (degradation and abnormal folding of proteins, inadequate energy production in CNS degeneration by oxidative damage, excitotoxicity and inflammation), there is interest in whether the AO, or changes in eating habits can prevent and/or block one or more of these pathways of neurodegeneration in slowing the progression of the disease (Mazzio, et al, 2011). In this regard, several studies have suggested some properties of antioxidants as protective factors against the risk of diseases such as AD and PD.…”
Section: Dietary Supplements With Antioxidant Used In the Management mentioning
confidence: 99%
“…In addition, due to the critical role that these nutrients play in the metabolism of glucose and mitochondrial respiration justifies the use of B vitamins for patients with PD (Mazzio et al, 2011). Some authors argue that a relationship exists between the PD, vitamin B6, vitamin B12 and folic acid.…”
Section: Vitamin Bmentioning
confidence: 99%
See 2 more Smart Citations